Potential for critical mineral deposits in Maine, USA - Slack, John F.; Beck, Frederick M.; Bradley, Dwight C.; Felch, Myles M.; Marvinney, Robert G.; Whittaker, Amber T.H. (Atlantic Geoscience, 2022)
An analysis of the potential for deposits of critical minerals and elements in Maine presented here includes data and discussions for antimony, beryllium, cesium, chromium, cobalt, graphite, lithium, manganese, niobium, platinum group elements, rhenium, rare earth elements, tin, tantalum, tellurium, titanium, uranium, vanadium, tungsten, and zirconium. Deposits are divided into two groups based on geological settings and common ore-deposit terminology. One group consists of known deposits (sediment-hosted manganese, volcanogenic massive sulphide, porphyry copper-molybdenum, mafic- and ultramafic-hosted nickel-copper [-cobalt-platinum group elements], pegmatitic lithium-cesium-tantalum) that are in most cases relatively large, well-documented, and have been explored extensively in the past. The second, and much larger group of different minerals and elements, comprises small deposits, prospects, and occurrences that are minimally explored or unexplored. The qualitative assessment used in this study relies on three key criteria: (1) the presence of known deposits, prospects, or mineral occurrences; (2) favourable geologic settings for having certain deposit types based on current ore deposit models; and (3) geochemical anomalies in rocks or stream sediments, including panned concentrates. Among 20 different deposit types considered herein, a high resource potential is assigned only to three: (1) sediment-hosted manganese, (2) mafic- and ultramafic-hosted nickel-copper(-cobalt-platinum group elements), and (3) pegmatitic lithium-cesium-tantalum. Moderate potential is assigned to 11 other deposit types, including: (1) porphyry copper-molybdenum (-rhenium, selenium, tellurium, bismuth, platinum group elements); (2) chromium in ophiolites; (3) platinum group elements in ophiolitic ultramafic rocks; (4) granite-hosted uranium-thorium; (5) tin in granitic plutons and veins; (6) niobium, tantalum, and rare earth elements in alkaline intrusions; (7) tungsten and bismuth in polymetallic veins; (8) vanadium in black shales; (9) antimony in orogenic veins and replacements; (10) tellurium in epithermal deposits; and (11) uranium in peat.